A modified El-Haddad model for versatile defect tolerant design. (April 2021) - Sheridan, Luke
Highlights: Stress Intensity Factor-Life (SIF-N) relationship derived and demonstrated. SIF-N model used to approximate fatigue crack growth models for AM materials. El-Haddad model extended to finite life across multiple stress ratios. Error calculations show little difference between NASGRO and Paris-based El-Haddad formulations. Crack growth model approximations compare well to experimentally determined data. Abstract: Defect tolerant design has played a significant role in the aerospace industry for qualifying new materials and retiring legacy components. One tool used in this design framework, the El-Haddad model, demonstrates how fatigue limit stress changes with respect to the size of a material defect. This paper enhances the legacy model to include finite life behavior and stress ratio effects. This enhancement is vetted against literature data from numerous sources, and it is shown quantitatively that the improved model accurately approximates crack growth rate behavior and represents in(finite) fatigue life of experimental components across multiple load ratios and defect sizes.